Ecotranslatology-based Research on the Strategies and Methods for Translating English Film Titles into Chinese - Yin, Rongrong; Tian, Chuanmao (International Journal of Humanities and Education Development (IJHED), 2020)
This paper explores the English film title translation strategies and methods through the theory of Eco-translatology proposed by Hu Gengshen. It studies the theme from three dimensions which are linguistics, culture and communication. And it can be seen that Darwin’s tenet of “natural selection and survival of the fittest” is fully employed in the theory. It is hoped that Eco-translatology can be better used in the market of film translation and other translation markets.